2010
DOI: 10.1002/jcla.20396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the alkaline wash/lysis procedure for the molecular diagnosis of a positive bacterial blood culture in clinical routine practice

Abstract: Blood culture is commonly used to detect microorganisms in patients with a suspected blood infection. This study evaluated the alkaline wash/lysis procedure to extract DNA of microorganisms in a clinical blood culture. A multiplex polymerase chain reaction (PCR) targeting the 16S rDNA (ribosomal DNA) gene and the fungal ITS (internal transcribed spacer) gene was used as a reliable indicator for the presence of microorganism DNA in the extracts. A total of 535 BacT/ALERT positive blood culture bottles were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The assay, which includes human gene RNase P as an internal control, has been optimized to circumvent the inhibitors present in the broth of Bactec bottles and to be completed in less than 4 h. This assay also showed that once BSA fraction V (96%) was utilized as an inhibitor reliever, no manipulation of the samples was required before or after manual or automated extraction, as previously reported (10,14).…”
Section: Discussionmentioning
confidence: 73%
“…The assay, which includes human gene RNase P as an internal control, has been optimized to circumvent the inhibitors present in the broth of Bactec bottles and to be completed in less than 4 h. This assay also showed that once BSA fraction V (96%) was utilized as an inhibitor reliever, no manipulation of the samples was required before or after manual or automated extraction, as previously reported (10,14).…”
Section: Discussionmentioning
confidence: 73%